Challenges in Diagnosing Diaphyseal Osteosarcoma – Importance of Strong Clinical Suspicion and Biopsy Technique: An Illustrative Case Report - V Balaji; Mohammed Tavfiq; Subalakshmi Balasubramanian; J K Giriraj Harshavardhan; Sabare Naaharaaj (Journal of Orthopaedic Case Reports)
Introduction: Osteosarcoma is the most common primary malignant bone tumor in adolescents, typically affecting the metaphyseal region of long bones. Diaphyseal osteosarcoma is rare and often mimics benign conditions such as osteomyelitis, leading to diagnostic delays. Case Report: A 17-year-old boy presented with progressive left thigh pain and swelling for 3 months. He had a trivial injury to left thigh 7 months back while playing kabaddi. Initial radiographs, computed tomography (CT), and magnetic resonance imaging showed a lytic intramedullary lesion with cortical thickening, suggestive of osteomyelitis. CT-guided biopsy also revealed features consistent with chronic osteomyelitis. Later debridement with open biopsy confirmed increased reactive osteoclastic giant cells, suggestive of chronic healed osteomyelitis. Despite empirical antibiotic treatment, symptoms worsened. A second open biopsy with intraoperative frozen section (FS) revealed features of high-grade osteosarcoma. Histopathological confirmation and immunohistochemistry with SATB2 established the diagnosis. The patient was treated with neoadjuvant chemotherapy followed by resection and femur reconstruction with a custom prosthesis. Discussion: This case illustrates the diagnostic pitfalls associated with diaphyseal osteosarcoma, especially in post-traumatic settings. It has also been observed in previous research studies that early overlapping clinical and radiological features with osteomyelitis often result in misdiagnosis. Needle biopsies, while minimally invasive, may yield non-representative samples, especially in heterogeneous tumors. Open biopsy targeting the lesion’s transition zone, supported by intraoperative FS, enhances diagnostic accuracy and enables timely intervention. Conclusion: In atypical presentations of musculoskeletal pain and swelling unresponsive to conservative treatment, malignancy should be suspected. A multidisciplinary approach, early advanced imaging, and appropriately planned biopsies are critical for accurate diagnosis and effective management of osteosarcoma.